Data mining and statistics for decision making - Tuffery, Stéphane. (Wiley series in computational statistics., 2011)
"Data Mining is a practical guide to understanding and implementing data mining techniques, featuring traditional methods such as cluster analysis, factor analysis, linear regression, PLS regression and generalised linear models"--